A Historical Review of Ronggo Prawirodirjo III’s Rebellion Against Dutch Colonialism in 1810 AD: A Critical Examination of Its Failure and Influence - Prasetya, Restu Dimas (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
This study, explained about rebellion of Ronggo Prawirodirjo III , Regent Of Madiun to Dutch Colonialist at 1810 AD. This study focuss at this rebel s failed factor and his influence to next historical moment. At this study, method that used is research historical method by Louis Gottschalk. From this study, we can know Ronggo Prawirodirjo III rebel to Dutch Colonialist at 1810 AD, and he failed because several factor, such as mess strategy and his power don’t match with Dutch Colonialist Power,. After this rebellion, Javanese Kingdom weakened and Europeans influence strengthen at Java.And his rebellion have big influence to next historical moment, War Of Java at 1825-1830 AD. At this war, Ronggo s son, Sentot became one Diponegoro s best commander and Diponegoro make Ronggo as his role model and inspiration.. Ronggo s rebellion, is rebellion that failed but have big influence at next Historical Moment.